A Man Dying With AIDS: Psychoanalysis or Existentialism? (Existential Analysis: Journal of the Society for Existential Analysis, 1998)
The aim of this paper is to develop an existentialist critique of psychoanalysis which has contemporary and practical relevance. It does this by drawing on a case-study of a man dying with AIDS published by Hildebrand in 1992. The interpretations proposed by Hildebrand are outlined and a critique and alternative explanation developed on the basis of the author's empirical research with HIV-positive individuals which is informed by an existentialist theoretical framework. It is argued that the latter framework provides the basis for a more valid, convincing and humane understanding of the situation faced by individuals living and dying with HIV/AIDS. The therapeutic implications of these alternative theoretical frameworks are discussed.